The Growth, Decline, and Transformation of the Diaconal Ministry and the Role of Women Deaconesses in the Early Churches - Kim, Eunha (Religions, 2023)
The objective of this article is to restore the credibility of the church within society by reestablishing its public role. Through the study of the lives and activities of women ministers in early Christianity, the research reveals that early Christianity initially granted equal authority to the ministries of diakonia (service to society) and the ministry of the Word, but gradually diminished the role of diakonia while stripping women of their status and authority. Therefore, to fully reinstate the genuine spirit of Christ, it is emphasized that the Korean church must regain the church’s public presence and recover the spirit of Jesus within the scattered congregations that currently exist.